2013
DOI: 10.1155/2013/517698
|View full text |Cite
|
Sign up to set email alerts
|

Sanguinarine Inhibits Vascular Endothelial Growth Factor Release by Generation of Reactive Oxygen Species in MCF-7 Human Mammary Adenocarcinoma Cells

Abstract: The inhibitory action and the possible mechanism of anticancer compound Sanguinarine (SAN) on vascular endothelial growth factor (VEGF) in human mammary adenocarcinoma cells MCF-7 were evaluated in this study. We exposed MCF-7 to SAN for 24 h, then cell viability was assessed by using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction assay. Human VEGF was measured using a paired antibody quantitative ELISA kit, relative expression of VEGF mRNA was calculated using the real-time P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Consistently, pre-treatment of tumor cells with antioxidants such as N-acetylcysteine or glutathione counteracts the apoptosis induced by sanguinarine [21,32,37,52] . Moreover, the over-expression of cyclooxygenase-2 (COX-2) also rescues prostate cancer cells from sanguinarine-induced apoptosis by sanguinarine enhances apoptosis in human mammary adenocarcinoma MCF-7 through the inhibition of VEGF release, induced by generation of ROS [32] . Sanguinarine also inhibits angiogenesis in preclinical experimental tumor models, such as mouse melanoma [48] and rat colorectal cancer, as we reported previously [49] .…”
Section: Sanguinarine-induced Apoptosis Through the Generation Of Reamentioning
confidence: 80%
See 1 more Smart Citation
“…Consistently, pre-treatment of tumor cells with antioxidants such as N-acetylcysteine or glutathione counteracts the apoptosis induced by sanguinarine [21,32,37,52] . Moreover, the over-expression of cyclooxygenase-2 (COX-2) also rescues prostate cancer cells from sanguinarine-induced apoptosis by sanguinarine enhances apoptosis in human mammary adenocarcinoma MCF-7 through the inhibition of VEGF release, induced by generation of ROS [32] . Sanguinarine also inhibits angiogenesis in preclinical experimental tumor models, such as mouse melanoma [48] and rat colorectal cancer, as we reported previously [49] .…”
Section: Sanguinarine-induced Apoptosis Through the Generation Of Reamentioning
confidence: 80%
“…In detail, it has been reported that micromolar concentrations of sanguinarine are capable of inhibiting tumor cell growth, and this inhibitory effect is associated with cell cycle arrest and induction of apoptosis [19][20][21][22] . The anti-proliferative and/ or pro-apoptotic activities of sanguinarine have been demonstrated in in vitro studies on several cancer cell types including epidermal [23] , keratinocyte [24,25] , prostate [26][27][28] , cervical [29] , breast [20,[30][31][32][33] , leukaemia [34,35] , lymphoma [36] , melanoma [37][38][39] , colon [40,41] , colorectal [21] , gastric [42] , pancreatic [19] , lung [22] , neuroendocrine [43] , osteosarcoma [44] , and human neuroblastoma cells [45] . By contrast, there are few studies on the in vivo effectiveness of sanguinarine administration per os [46,47] in animal tumor models [33,48] .…”
Section: Sanguinarine Induces Apoptosis In Tumor Cellsmentioning
confidence: 99%
“…One testable hypothesis is that since HMOX1 generates carbon monoxide (CO) through enzymatic reaction, it can alter the metabolic state of GBM cells and offset cellular respiration under hypoxic conditions, which would promote the survival and maintenance of CSCs in a nondifferentiated state. In general CO has a cytoprotective effect since it limits excessive production of toxic reactive oxygen species (ROS) in mitochondria by inducing a mild‐uncoupling state .The cytoprotective effect of HMOX1 through CO generation could be adopted by CSCs to reduce ROS levels and survive in the hypoxic region of the tumor. If so, understanding the mechanism for ROS regulation in CSCs may help in the development of powerful therapeutic strategies in future.…”
Section: Discussionmentioning
confidence: 99%
“…Given that these compounds were identified as inhibitors of RGS17 and that these compounds have reported activities in lung, prostate, hepatocellular carcinoma, and breast cancer, the pathologies in which RGS17 has been reported to play a role, it is possible that inhibition of RGS17 may be one of the many mechanisms by which these compounds alter cancer cell growth. 5658 Extensive pathway analysis is required to determine exactly what signaling events are being altered in the lung and prostate cell lines used here to determine the primary mechanism of action of these compounds.…”
Section: Resultsmentioning
confidence: 99%